METHODOLOGICAL BASES OF RESEARCH OF MODERN SPIRITUAL-INFORMATION SPACE - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
In this article, the main approaches to the analysis of the structural and dynamic processes occurring in the spiritual space of our time are examined. The specifics of the current state of public consciousness are shown. The epistemological significance of the dialectic law of negation of negation is substantiated in its constructive form of removing contradictions.